A Combination of Action Research and Reflective Journal Writing in an English as a Foreign Language Class: Learners’ Psychological Point of Views and Their Grammar Use in Writing - Tahmasbi, Soheila; Karimnia, Shabnam; Rahimi, Ali (Frontiers in Psychology, 2022)
Action research (AR) and reflective thinking (RT) can enhance learning since both processes provide students with the opportunities to step back and think about how they actually solve problems. While there is a robust academic inquiry on reflection practices and AR in the educational setting, investigating learners’ reflections through AR practices can shed more light on related research. This study implemented reflective journal writing through AR and aimed to investigate (1) the participants’ views about reflective journal writing, (2) the effects of journal writing on RT development, and (3) the learners’ grammar use in writing. Eighty language learners formed the two experimental and control groups of the study. The possible relationship between the RT level and participants’ final exam was checked. Analyses of the participants’ journals, the semi-structured interview, the questionnaires’ results, and the final exam scores were considered. The findings showed that the participants had positive views about journal writing, and they could enhance their level of RT as well as their grammar use in writing; nevertheless, no relationship between the RT level and final exam scores of the participants was found. The methodology and the results of the study could be conducive to welcoming alternative methods of teaching and assessment that encourage the learners’ reflective practices and active engagements in language classes.